Hubungan Pemberian Pekerjaan Rumah (PR) dengan Prestasi Belajar Mata Pelajaran Pendidikan Agama Islam Siswa SDN Kuanino Kecamatan Kota Raja Kota Kupang - Jihada, Ilfiana Iffah; Agusman (Prodi Pendidikan Agama Islam, 2022)
The purpose of this study was to determine the relationship between giving homework and PAI learning outcomes for students at SDN Kuanino, 2014/2015 academic year. The method in this research is correlational research. The sample used in this study was a saturated sample, that is, all the population studied were 26-1=25 students in grades III, IV and V at SDN Kuanino. Data collection techniques for variable X (Providing Homework) that is by using a questionnaire or questionnaire which is presented in the form of a statement consisting of 25 statements that have been tested through validity and reliability tests. To find out the significance of the relationship, a t-test was carried out, namely to get the results of rcount > rtable where ttable was at a significance level of 0.05 with dk (n-2) = (25-2) = 23 of 1.714, with test criteria Ho: rejected if tcount> ttable and Ho: accepted if tcount> ttable, because tcount = 4,943 > 1,714 rejected. Thus, it can be concluded that there is a significant relationship between giving homework and PAI learning outcomes for students at SDN Kuanino, Kupang City.